Strategies and techniques for crafting a scientific manuscript for artistic publication: a guide for academic artists in Indonesia - Sularso Sularso; Agus Cahyono; Qinyu Yu; Joko Suranto; Zulkarnain Mistortoify; Lardianto Budhi (International Journal of Visual and Performing Arts, 2024)
Scientific publications in the field of art creation have sparked considerable debate within the academic community in Indonesia. Issues such as the validity of artworks, assessment criteria, publication formats, and the alignment of academic standards with artistic practice have generated discussions regarding the format of publication writing. This article aims to offer alternative guidance on techniques for writing scientific publication articles in the field of art creation, particularly tailored for academic artists in Indonesia. The guidance encompasses a literature review, the selection of an appropriate methodology, the provision of relevant examples and illustrations, the application of a reflective analytical approach, the clear presentation of data and results from art creation research, as well as the development of an appropriate writing structure and language. Through this study, academic artists in Indonesia stand to benefit significantly. First, they can enhance the quality of their publications by adhering to the provided writing technique guidelines. These guidelines will aid in fortifying the substance of their articles, organizing data in a structured manner, and conveying thoughts and ideas more clearly and effectively. Second, by employing this guide, academic artists can improve their ability to disseminate their thoughts, ideas, and artistic knowledge more widely. This will enable them to contribute to the global arts community through high-quality scientific publications. By enhancing the quality of publications and fostering more effective dissemination of ideas, this research will contribute to the development and recognition of Indonesian academic artists on the global stage. Through the enhancement of publication quality and the improved dissemination of artworks, Indonesian academic artists will be better positioned to make significant contributions.